ASSESSMENT TECHNIQUES OF ENGLISH SUBJECT FOR YOUNG LEARNERS BY TEACHERS AT AL-AZHAR ELEMENTARY SCHOOL IN JAMBY CITY - lilis handayani (JAMBI-ENGLISH LANGUAGE TEACHING, 2023)
The purpose of this research is to explore how the way young learners’ teachers assess young learners in English subject. The participants of this research were teachers at Al-Azhar elmentary school in Jambi city because they had applied English as an additional subject. The qualitative research was used in this research with a case study approch to collect the data. The instrument used by the researcher to collect data was interview in order to explore about how young learners teachers’s assess young learners in English study. In this research, participant also explain about the reason they use those assessment techniques. The assessment techniques that young learners teachers’s use is test and observation. The researcher found that the reason of the participants use test as technique to assessing young learners is easy and effective. Meanwhile observation is more natural for daily assessment. The last is pair assessment that has purpose to give courage to young learners to give opinion or comment. The finding have purpose to realize there is many techniques to assessing young learners.   Keywords:, Assessment, Techniques, Young learners